4x2-9-2(2x+3)=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3}{x^3-1}=\frac{3}{\left(x-1\right)\left(x^2+x+1\right)}\)( ĐKXĐ : x ≠ 1 )
\(\frac{2x}{x^2+x+1}\)( ĐKXĐ : x ∈ R )
\(\frac{x}{x-1}\)( ĐKXĐ : x ≠ 1 )
MTC : ( x - 1 )( x2 + x + 1 )
=> \(\frac{3}{x^3-1}=\frac{3}{\left(x-1\right)\left(x^2+x+1\right)}\)
=> \(\frac{2x}{x^2+x+1}=\frac{2x\left(x-1\right)}{\left(x-1\right)\left(x^2+x+1\right)}=\frac{2x^2-2x}{\left(x-1\right)\left(x^2+x+1\right)}\)
=> \(\frac{x}{x-1}=\frac{x\left(x^2+x+1\right)}{\left(x-1\right)\left(x^2+x+1\right)}=\frac{x^3+x^2+x}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(\frac{1}{-x^2+3x-2}=\frac{-1}{x^2-3x+2}=\frac{-1}{x^2-x-2x+2}=\frac{-1}{x\left(x-1\right)-2\left(x-1\right)}=\frac{-1}{\left(x-1\right)\left(x-2\right)}\)
( ĐKXĐ : x ≠ 1 ; x ≠ 2 )
\(\frac{1}{x^2+5x-6}=\frac{1}{x^2-x+6x-6}=\frac{1}{x\left(x-1\right)+6\left(x-1\right)}=\frac{1}{\left(x-1\right)\left(x+6\right)}\)
( ĐKXĐ : x ≠ 1 ; x ≠ -6 )
\(\frac{1}{-x^2+4x-3}=\frac{-1}{x^2-4x+3}=\frac{-1}{x^2-x-3x+3}=\frac{-1}{x\left(x-1\right)-3\left(x-1\right)}=\frac{-1}{\left(x-1\right)\left(x-3\right)}\)
( ĐKXĐ : x ≠ 1 ; x ≠ 3 )
MTC : ( x - 1 )( x - 2 )( x - 3 )( x + 6 )
=> \(\frac{-1}{\left(x-1\right)\left(x-2\right)}=\frac{-1\left(x+6\right)\left(x-3\right)}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}=\frac{-x^2-3x+18}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}\)
=>\(\frac{1}{\left(x-1\right)\left(x+6\right)}=\frac{1\left(x-2\right)\left(x-3\right)}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}=\frac{x^2-5x+6}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}\)
=> \(\frac{-1}{\left(x-1\right)\left(x-3\right)}=\frac{-1\left(x-2\right)\left(x+6\right)}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}=\frac{-x^2-4x+12}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x+6\right)}\)
\(\frac{1}{x^2-2x+1}=\frac{1}{\left(x-1\right)^2}\)( ĐKXĐ : x ≠ 1 )
\(\frac{2}{x^2+2x}=\frac{2}{x\left(x+2\right)}\)( ĐKXĐ : x ≠ 0 ; x ≠ -2 )
MTC : x( x + 2 )( x - 1 )2
a) x2 + 7x + 12
= x2 + 3x + 4x + 12
= ( x2 + 3x ) + ( 4x + 12 )
= x( x + 3 ) + 4( x + 3 )
= ( x + 3 )( x + 4 )
b) x4 + 8x2 + 16
= ( x2 )2 + 2.x2.4 + 42
= ( x2 + 4 )2
c) x2 + 26x + 25
= x2 + x + 25x + 25
= ( x2 + x ) + ( 25x + 25 )
= x( x + 1 ) + 25( x + 1 )
= ( x + 1 )( x + 25 )
a) \(x^2+7x+12\)
\(x^2+4x+3x+12\)
\(x\left(x+4\right)+3\left(x+4\right)\)
\(\left(x+4\right)\left(x+3\right)\)
b) \(x^4+8x^2+16\)
\(\left(x^2+4\right)^2\)
c) \(x^2+26x+25\)
\(x^2+x+25x+25\)
\(x\left(x+1\right)+25\left(x+1\right)\)
\(\left(x+25\right)\left(x+1\right)\)
\(2x^2+4y^2-4xy+x-4y=-\frac{5}{4}\)
\(\Leftrightarrow\text{}x^2-x+\frac{1}{4}+x^2-2x\left(2y-1\right)+4y^2-4y+1=0\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right)^2+\left(x-2y+1\right)^2=0\)
\(\Leftrightarrow\hept{\begin{cases}x-\frac{1}{2}=0\\x-2y+1=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=\frac{1}{2}\\y=\frac{3}{4}\end{cases}}}\)
4x2 - 9 - 2(2x + 3) = 0
=> 4x2 - 4x - 15 = 0
=> 4x2 - 4x + 1 - 16 = 0
=> (2x - 1)2 - 42 = 0
=> (2x - 1 - 4)(2x - 1 + 4) = 0
=> (2x - 5)(2x + 3) = 0
=> \(\orbr{\begin{cases}2x-5=0\\2x+3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{5}{2}\\x=-\frac{3}{2}\end{cases}}\)
Vậy \(x\in\left\{\frac{5}{2};-\frac{3}{2}\right\}\)là giá trị cần tìm
4x2-9-2(2x+3) =0
(2x)2 -32 -2(2x+3) = 0
(2x + 3)(2x - 3) -2(2x+3) = 0
(2x + 3)(2x - 3 - 2) =0
\(\orbr{\begin{cases}2x+3=0\\2x-3-2=0\end{cases}}\)\(\orbr{\begin{cases}2x=-3\\2x=5\end{cases}}\)\(\orbr{\begin{cases}x=\frac{-3}{2}\\x=\frac{5}{2}\end{cases}}\)